Connecting Health and Technology (CHAT): protocol of a randomized controlled trial to improve nutrition behaviours using mobile devices and tailored text messaging in young adults - Kerr, Deborah; Pollard, Christina; Howat, Peter; Delp, E.; Pickering, M.; Kerr, Katherine; Dhaliwal, Satvinder; Pratt, Iain; Wright, Janine; Boushey, C. (BioMed Central Ltd, 2012)
Background: Increasing intakes of fruits and vegetables intake, in tandem with reducing consumption of energy-dense and nutrient poor foods and beverages are dietary priorities to prevent chronic disease. Although most adults do not eat enough fruit and vegetables, teenagers and young adults tend to have the lowest intakes. Young adults typically consume a diet which is inconsistent with the dietary recommendations. Yet little is known about the best approaches to improve dietary intakes and behaviours among this group. This randomised controlled trial aims to evaluate the effectiveness of using a mobile device to assess dietary intake, provide tailored dietary feedback and text messages to motivate changes in fruit, vegetable and junk food consumption among young adults.